Management in pesantren education institutions - Reyhan Fachrizal, Muhammad; Aulya Safitri, Nabila; Fitriani, Rifda; Syarifudin, H. E. (Educenter : Jurnal Ilmiah Pendidikan, 2023)
An education in the form of boarding school is very important to implement its management. The management pattern in boarding school education is able to run and stabilize a boarding school. The purpose of this research will simply discuss some explanations regarding the management system applied in boarding schools. The method used for the essence of this article uses the heritage study method. The results show that management in boarding schools involves human resources and non-human resources to achieve educational goals effectively and efficiently. Kyai as an educational leader in pesantren has a unique task, not only as a curriculum planner, compiler of regulations and evaluation systems, and teacher of Islamic religious knowledge, but also as a leader and educator of the people and society. The change of leaders in pesantren is mostly natural, occurring due to the death of pesantren leaders or hereditary, and not planned. The pattern of changing leaders in pesantren is also mostly natural, such as the death of the pesantren leader, the replacement takes place flexibly.